Female Police Officers and Their Experiences: The Metropolitan Police of Buenos Aires Context. Issue 4 (8th August 2017) - Colvin, Roddrick
Abstract : This research explores the experience of female police officers in the Metropolitan Police of Buenos Aires, which began providing public safety in 2010. The purpose of this research is to better understand the barriers and opportunities female officers are encountering in this new context of community policing in Latin America. With better understanding, law enforcement officials will be better equipped to ensure that female officers achieve at the highest levels in organizations. Responding female officers identified civic duty as a primary reason for joining the force. Female officers did not report significant levels of institutional discrimination but did report informal disparaging treatment, including sexual harassment. The results of this research suggest that as this young police force matures, officials should pay close attention to the emerging culture of the organization, as many common and negative aspects of it have already started to form.